Advances in Cell Therapy Using Rabbit Models for Regenerative Medicine - , Maria Vitória da Silva Xavier, Bruna Larissa Bernardo de Lima, José Sérgio Herculano Gomes da Silva, Elton Santos Guedes de Morais, Mariza Brandão Palma, Anísio Francisco Soares (Archives of Current Research International, 2024)
Cell therapy represents an innovative and promising approach to treating debilitating conditions, and animal testing on rabbits has played a crucial role in advancing this therapy. The objective of this manuscript aims to review the literature on the use of lagomorphs in cell therapy studies. The Pubmed and ScienceDirect databases were used, with the descriptors: Cell therapy and experimentation in rabbits; rabbits and cell therapy. After an initial retrieval of 1799 articles, those that did not specifically address the use of rabbits in cell therapy or were unrelated to the scope of this review were excluded. This resulted in a final selection of 21 articles. The present work presents a broad and distinct view of cell therapy and its different applicability, presenting a promising framework for animal experimentation in rabbits, and the advantages of using this animal model.